If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -3x + 4 = 0 Reorder the terms: 4 + -3x + y = 0 Solving 4 + -3x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -3x + -4 + y = 0 + -4 Reorder the terms: 4 + -4 + -3x + y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x + y = 0 + -4 -3x + y = 0 + -4 Combine like terms: 0 + -4 = -4 -3x + y = -4 Add '-1y' to each side of the equation. -3x + y + -1y = -4 + -1y Combine like terms: y + -1y = 0 -3x + 0 = -4 + -1y -3x = -4 + -1y Divide each side by '-3'. x = 1.333333333 + 0.3333333333y Simplifying x = 1.333333333 + 0.3333333333y
| 2(y-7)-3y=-(y-3)-12 | | Tan(4*x)=0 | | 3x+(x+5)=70 | | 2x-12+3(x-3)=5+x+2(x-6) | | 3x+(x+4)=70 | | 3y^2+2y-10=0 | | -1/6*9-7 | | 4y + 3 = 2y + 8 | | 6(f+4)=18 | | 4y + 3 = 2y + 9 | | 6x - 5 = 2x + 9 | | 4y + 1 = 2y + 8 | | -8x^4+24x^2-6=0 | | 40 - x = 4 + x | | 2(2l+2)=36 | | 240=20x+30y | | (u-3)*9=18 | | 20y - 16 = 18y - 9 | | -9a+4=24 | | (q-6)*2=18 | | 5p + 7 = 3( 4 - p ) | | y=1/3bh | | 7r + 2 = 5( r - 4 ) | | 7p + 2 = 5p + 8 | | 8x^2+8x+10=0 | | 5g+4f-2f+3g= | | f(x)=-16x^2+50x-25 | | 7r + 3 = 3( r - 1 ) | | 6p - 5 = 2p + 7 | | 12a + 2 = 2a - 6 | | (6x-5)(x-3)=2x(3x+4) | | sqrt(5x+1)-sqrt(4x+3)=x |